Changes in Macroeconomic conditions and capital Return in Indonesia - Andesta Selvi; Adam Mohammad; . Suhel (Модернизация, инновация, развитие, 2020)
Purpose: this study aims to examine the influence of changes in inflation, changes in the rupiah exchange rate, changes in the money supply, changes in SBIS, changes in foreign exchange reserves and changes in interest rates on the return of Indonesian Islamic stocks.Methods: this study is focused on looking at conditions of macroeconomic changes that have an impact on the activity of the Islamic capital market, particularly on the return of Islamic stocks listed in the Jakarta Islamic Index. This empirical evidence is related to variable macroeconomic changes, namely changes in inflation, rupiah exchange rate, money supply, foreign exchange reserves, Indonesian Syariah Bank Certificates (SBIS) and interest rates on sharia stock returns for the period January 2014 – December 2019 obtained from Financial publications. Service Authority (OJK) and Bank Indonesia. The analysis technique used is quantitative analysis using multiple regression analysis tools.Results: the results of this study are (1) Variable Changes in Inflation, Changes in the Amount of Money Supply, Changes in Foreign Exchange Reserves, Changes in SBIS have a positive and significant effect on Stock Returns listed on the Jakarta Islamic Index, (2) changes in exchange rates have a negative and significant effect on Stock Returns listed in Jakarta Islamic. Index, (3) the Interest Rate variable has no effect on Stock Returns listed on the Jakarta Islamic Index.Conclusions and Relevance: the approach used by each variable starts with the conventional followed by the study of Islamic macroeconomics, in order to provide a philosophy of science and economics that refers to Baqir Sadr in the Iqtishaduna book. In this study, researchers examined macroeconomic variables on sharia stock returns to prioritize people's welfare and pay close attention to every investment process based on sharia principles. Therefore the public, entrepreneurs, investors and company performance must pay attention to information regarding changes in inflation, changes in the rupiah exchange rate, changes in the money supply, changes in Bank Indonesia Sharia Certificates (SBIS), changes foreign exchange reserves, and changes in interest rates in order to minimize risks for both investors and entrepreneurs. This variable can affect the movement of the capital market so that the return on Islamic stocks also has an effect.